Replanteo y trazado del proyecto vertical de la carretera: cerecita - tamarindo - bajada del progreso: tramo # 1 desde abs. 0+000 hasta abs. 1+100. - Avilés De La Torre, Henry Wilson (2010)
Completed the redesign of the project layout and horizontal, is theRethinking the vertical project, it serves to make the strip clearing with the relevant equipment, then placed side earth-moving spot, and left at subgrade elevation, both made it a good study done by for the movement of soil from the subgrade, getting results would be optimal according to the design Then you can proceed with the redesign of the pavement, thickness, height of subbase, base coat and the coat of the folder track, in which using another type of heavy duty machinery, here you must have a good knowledge of equipment performance and use staking is can begin with the respective signage along the road preventing and regulate the use of the road.